2020
DOI: 10.1177/1369433220904011
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical assessment of the flexural behaviour of semi-precast-reinforced concrete slabs

Abstract: Semi-precast-reinforced concrete slab system offers more economic method of construction as it minimises the need of formwork at site. The assembly of semi-precast slab system involves two steps: (1) casting of semi-precast slab at the yard and (2) overtopping of concrete at the site. One of the main factors that influence the performance of such slab system is the interface bonding between precast and overtopping concrete. Therefore, in order to better understand the performance of this slab system, a researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 37 publications
(37 reference statements)
0
9
0
4
Order By: Relevance
“…Būdingiausios surenkamosios monolitinės perdangos plokštės su plastikiniais intarpais vietos, kuriose anksčiausiai susidaro plyšiai, yra atraminė zona (Hegger et al, 2003;Ji & Liu, 2020), plokštės surenkamajame sluoksnyje ties didžiausio lenkimo momento vieta (Mohamed et al, 2020) ir surenkamojo ir monolitinio betono sluoksnių jungtyje (Mohamed et al, 2020;Ibrahim et al, 2019). Irimas atraminėje zonoje ir betono sluoksnių jungtyje gali susidaryti dėl didelio lenkimo momento ir šlyties įtempių.…”
Section: įVadasunclassified
See 2 more Smart Citations
“…Būdingiausios surenkamosios monolitinės perdangos plokštės su plastikiniais intarpais vietos, kuriose anksčiausiai susidaro plyšiai, yra atraminė zona (Hegger et al, 2003;Ji & Liu, 2020), plokštės surenkamajame sluoksnyje ties didžiausio lenkimo momento vieta (Mohamed et al, 2020) ir surenkamojo ir monolitinio betono sluoksnių jungtyje (Mohamed et al, 2020;Ibrahim et al, 2019). Irimas atraminėje zonoje ir betono sluoksnių jungtyje gali susidaryti dėl didelio lenkimo momento ir šlyties įtempių.…”
Section: įVadasunclassified
“…Kitų autorių tyrimų (Ibrahim et al, 2019;Stehle et al, 2011;Mohamed et al, 2020;Hegger et al, 2003) analizė parodė, kad galima išskirti tris tokio tipo plokščių darbo etapus. Pirmajame etape konstrukcija dirba tampriai, dar nėra pasireiškusios plastinės deformacijos.…”
Section: įVadasunclassified
See 1 more Smart Citation
“…It was reported that the ductility and toughness improved with the addition of steel fibre reinforced toppings to the precast concrete slab. Mohamed et al (2020) assessed the flexural performance of semi-precast slabs with in situ concrete slabs with different interface detailing and shear ties. The study reported that the type of surface treatment has pronounced influence on the flexural capacity of composite slab systems tested.…”
Section: Introductionmentioning
confidence: 99%
“…A number of sources [ 1 , 4 , 7 , 8 , 9 ] provide that at the initial service stage of loads affecting the above introduced structures, both layers work and deform together until loads reach 50% of bearing capacity. Conventional structural analysis applies to the previously mentioned slabs because the slab has the same load-bearing capacity as a monolithic reinforced concrete slab of the solid cross-section [ 3 , 4 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%